Multiple renal and liver cysts in a Siberian hybrid tiger - Fraser, Charisha; Zulhisam, Atiqah; Akmal, Mohd Noor; Saad, Mohd Zamri; Salleh, Annas (Chiang Mai University, 2023)
Polycystic kidney disease (PKD) is an inherited disease commonly reported in cats, but rarely in big cats. It is associated with formation of cysts in the kidneys. This article describes the clinical, pathology and immunohistochemistry findings of PKD in a Siberian hybrid tiger. A 16-year-old female captive Siberian hybrid tiger showed inappetence, weight loss, polyuria, and polydipsia. Within six months, its body weight and hydration status were progressively declining. Although hematology parameters were normal, serum creatinine and urea levels were elevated. Ultrasonography of the kidneys showed the presence of cysts. The animal was euthanized and necropsied, revealing multiple cysts in both kidneys and liver. These samples were subjected to histopathology using routine stain, special histochemistry, and immunohistochemistry. The cysts were lined by various types of epithelial cells. Most renal tubular epithelium showed severe vacuolar degeneration, accompanied by bacterial colonies in the renal pelvis. Masson’s trichrome stain demonstrated presence of mesenchymal stroma at the periphery of the cysts in the kidneys and liver. Immunohistochemistry showed different staining intensity of β-catenin, E-cadherin, and vimentin in the various parts of renal tubules, suggesting the involvement of epithelial-mesenchymal transformation. The tiger was diagnosed with PKD based on clinical and pathological examination. This is the first report of PKD in a tiger, potentially useful for future study in wildlife medicine and conservation.